Impact And Emergence of Web Technology and Learning Management System in Education - Amal Joseph (AG Volumes, 2022)
The higher education system is changing every day. The evolution and integration of technology into the higher education system will boost its efficiency and quality. Education is an important part of every human being. Education transfers the mind of a human. Education can help a person come from darkness into marvelous light. When education has a significant influence on the life of a person, technology can help him learn anywhere at any time. This paper discusses the impact and emergence of web technology and learning management systems on education. Web technologies are employed in a wide range of applications, from everyday living to space research. This chapter begins with the introduction to web-based technology-based education and a literature review. This paper includes web technology-based education and the structure of the web technology-based education system. There is a difference between web technology-based education and traditional education mentioned in this chapter. The journey from traditional education to modern or electronic learning has different norms and aspects. Today, students can learn at home at any time with the help of LMS, and teachers can reach the home of the student online. Google Meet, Zoom, Webx, and Microsoft Teams have played an important role in the COVID period. They helped the students and teachers turn their homes into virtual classrooms. The role of the teacher in developing a web technology-based education and the steps involved in the formulation of a course in the Learning Management System will help the readers to understand the procedures included in the development of an LMS. E-Learning has been developed to provide students with efficient technologies and tools that they need to finish their fundamental schooling and improve their learning abilities. The emerging role of technology in education makes learning more interactive, self-directed and independent. The chapter concludes with the main points taken from the chapter.